Parental Burnout in a Population of Beneficiaries to the Medical Service in Tabasco, Mexico. - López-Ramírez, Gabriel; Díaz-Sánchez, Nallely; Domínguez-Vega, Guadalupe Montserrat; Méndez-Flores, Orquidia G; Tejas-Juárez, Juan Gabriel (Horizonte Sanitario, 2024)
Objective: To determine the prevalence of Parental Burnout (PB) syndrome in the population of beneficiaries of a family clinic of the Mexican Social Security Institute (IMSS) in Villahermosa, Tabasco. This condition is characterized by the perception of insufficient of emotional, physical and material resources to achieve an effective parenting, therefore stress, chronic fatigue and depression occur in the affected parents. Material and Methods: During 2023, an observational, analytical, cross-sectional study was carried out with the aim of detecting cases of PB. The sample consisted of 268 beneficiaries aged 18 to 44, using the modified Spanish version of the PB Assessment as an evaluation instrument. Results: Upon evaluating the BP degrees of the studied population, it was found that 180 (67.2%) out of 268 beneficiaries presented mild BP. Regarding dimensions, exhaustion was the most prevalent, since mothers presented higher scores than fathers. Conclusions: BP is a result of chronic imbalance between risks and resources in the context of parenting. Mothers present significantly higher scores than fathers because mothers are still the main caregivers of their children; a fact associated with traditional gender roles that are still maintained. Keywords: Burnout; Parenting; Prevalence Rate; Population Characteristics.